FACTORS ASSOCIATED WITH CONDITION OF FRAILTY TO OLDERLY IN MANGUNJAYA VILLAGE - rizki damayanti, adelia dwi; Ahadi Pradana, Anung (STIKes Mitra Keluarga, 2024)
Introduction: Elderly people are individuals aged more than 60 years. As we get older, the body will experience an aging process which will increase the risk of weakness or frailty. Objective: to determine the factors associated with the condition of frailty in the elderly. Method: Using a cross sectional design carried out in June 2023 in Mangunjaya village. The sample for this study consisted of primary data totaling 110 elderly people based on the Slovin formula with predetermined inclusion and exclusion criteria. The instruments used were demographic data, Katz index, and frail scale. Data analysis used descriptive analysis with Pearson Chi Square and Fisher Exact correlation tests. Results: It was found that the age variable was related to the condition of frailty in the elderly (p-value = 0.031 < a(0.05)). However, gender (p-value = 0.563 > a(0.05)), education level (p-value = 0.805 > a (0.05)), socioeconomic (p-value = 0.608 > a (0.05)) , and daily activities (p-value = 0.578 > a (0.05)) there is no significant relationship with the condition of frailty. Conclusion: There is one variable that has a relationship with the condition of frailty in the elderly, namely age, and four variables have no relationship, namely gender, education level, socioeconomics, and daily activities. So it is hoped that future researchers will be able to pay attention to the characteristics of the elderly and develop similar research in the future.